A Synergistic Combination of DHA, Luteolin, and Urolithin A Against Alzheimer’s Disease - Jayatunga, Dona P. W.; Hone, Eugene; Fernando, W. M. A. D. Binosha; Garg, Manohar L.; Verdile, Giuseppe; Martins, Ralph N. (Frontiers in Aging Neuroscience, 2022)
Alzheimer’s disease (AD) is a devastating neurodegenerative disorder and the most common form of dementia worldwide. The classical AD brain is characterized by extracellular deposition of amyloid-β (Aβ) protein aggregates as senile plaques and intracellular neurofibrillary tangles (NFTs), composed of hyper-phosphorylated forms of the microtubule-associated protein Tau. There has been limited success in clinical trials for some proposed therapies for AD, so attention has been drawn toward using alternative approaches, including prevention strategies. As a result, nutraceuticals have become attractive compounds for their potential neuroprotective capabilities. The objective of the present study was to derive a synergistic nutraceutical combination in vitro that may act as a potential preventative therapy for AD. The compounds of interest were docosahexaenoic acid (DHA), luteolin (LUT), and urolithin A (UA). The cell viability and cytotoxicity assays MTS and LDH were used to evaluate the compounds individually and in two-compound combinations, for their ability to inhibit Aβ1–42-induced toxicity in human neuroblastoma BE(2)-M17 cells. The LDH-derived% protection values were used in the program CompuSyn v.1.0 to calculate the combination index (CI) of the two-compound combinations. The software-predicted potentially synergistic (CI < 1) two-compound combinations were validated using CellTiter Glo assay. Finally, a three-compound combination was predicted (D5L5U5) and shown to be the most effective at inhibiting Aβ1–42-induced toxicity. The synergistic combination, D5L5U5 warrants further research for its mechanism of action; however, it can serve as a basis to develop an advanced functional food for the prevention or co-treatment of AD.